Differences in 3D kinematics between volleyball and beach volleyball spike movements - Tilp, M.; Wagner, H.; Müller, E. (Sports Biomechanics, 2008)
The purpose of this study was to identify differences between volleyball and beach volleyball spike jump movements performed on an indoor surface and sand surface respectively. Eight elite male volleyball players performed spike jump movements on both surfaces. An eight-camera motion capturing system (250 Hz) was used to generate 3D kinematic data. Seven groups of variables representing the kinematics of the centre of mass, the countermovement, the approach phase, and the angular amplitudes and maximal velocities of the lower and upper limbs were examined using Hotelling's T 2/2 . Significant differences were observed in the movement of the centre of mass (P < 0.05), the countermovement, the kinematics of the approach phase, and the angular amplitudes of the lower limbs. However, no significant differences were observed either in the maximal angular velocities of the lower and upper limbs, or in the amplitudes of the upper limb motion. In conclusion, the participants showed significant adaptation to changed movement conditions. As a result of the compliance of the sand surface, the participants slowed down their movements, especially during the phase of transition from knee flexion to extension and during the extension phase. Furthermore, the participants demonstrated changes in foot position to reach the greatest height possible.